Kajian Kriminologi Terhadap Praktek Prostitusi Berkedok Bisnis Panti Pijat Di Kota Merauke - Mulyadi Alrianto Tajuddin (Jatiswara, 2016)
The study, entitled "Study of Criminology Against the Practice of Prostitution Business guise Massage parlor in the town of Merauke" As for the issues to be examined is how the view of criminology against prostitution under the guise of business parlors, factors What factors encourage prostitution under the guise of business of massage parlors in the town of Merauke, what efforts are being made to overcome the practice of prostitution under the guise of business massage parlors in the city merauke. While the purpose of this study was to investigate and analyze issues. To achieve the study researchers used a qualitative research method using juridical and empirical approach. The results showed that in terms of criminology prostitution is regarded as a crime against morality / decency and against the law. But prostitution is a crime but did not constitute a crime in the sight of the Criminal Code, the factors that encourage the practice of prostitution under the guise of business, the form factor that comes from within the individual and also factors outside the individual, efforts were made to prevent work under the guise of massage parlors prostitution business is by way of preventive and repressive.